Analysis of the Patient Registration Flow at the Eye Clinic of RS Dustira: an Evaluative Study on Efficiency and Patient Satisfaction - Aeny, Nurul; Susanti, Ai Susi (Asian Journal of Environmental Research, 2025)
This study aims to analyze the patient registration flow at the Eye Clinic of Dustira Hospital Cimahi, with a particular focus on the efficiency of service and the level of patient satisfaction. The background of this research lies in the increasing demand for quality and efficient healthcare services, especially in specialized outpatient clinics that serve high volumes of patients daily. The research was conducted using a qualitative descriptive method during the Field Work Practice (PKL) period, with data collection techniques consisting of direct observation of the registration process and semi-structured interviews with both administrative staff and patients. The findings show that the registration flow at the Eye Clinic has been arranged in a systematic manner, starting from the arrival of patients, queue number retrieval, identity verification, and input into the hospital information system. However, several issues were identified, such as long waiting times during peak hours and limited patient understanding of the available digital or online registration options. These factors were found to affect overall patient satisfaction. Despite the use of a structured system, the effectiveness of the registration process still depends on patient awareness and digital literacy. Therefore, the study recommends regular evaluation of the service workflow and the implementation of patient education programs regarding the use of digital registration tools. Improvements in communication, guidance signage, and staff support can further enhance service efficiency and ensure that patients receive timely and satisfactory care at the Eye Clinic.